ANTI-OXIDATIVE EFFECTS OF GYPSOPHILA PERFOLIATA ON DGALACTOSE INDUCED AGING IN RAT - Şahin, Korkut Furkan; Serdaroğlu Kaşikçi, Emel; Çevreli, Burcu; Zengin, Gokhan; Gözler, Tayfun; Konuk, Muhsin (Yildiz Technical University, 2020)
D-Galactose (D-GAL), a monosaccharide, induces the oxidative stress and results in the mimicked aging model in rats. Gypsophila perfoliata belongs to Caryophyllaceae family and a perennial plant. The content of this plant is rich in saponarin and Phenolics, therefore scientist has been focused on its possible antioxidative effects. In this study, we studied the antioxidant effect of Gypsophila perfoliata on aging mimicked rats induced by D-GAL. For this, Wistar-albino rats (n=8 in each group of 4) have been applied D-GAL (150 mg/kg/day) subcutaneously (s.c.) and Gypsophila extract (100 mg/kg/day) via gavage for 12 weeks. After this period, the rats were sacrificed and their blood serum and brains used to determine Glutathione (GSH) and Malondialdehyde (MDA). The data were analyzed by use of the SPSS software package (20th version) One-way ANOVAs followed by post-hoc Bonferroni tests were used, and p< 0.05 was considered as significantly different value. When the data of examined groups compared to the control, we observed a significant increase in the MDA while significant decrease in the GSH levels. However, when we compared the Gypsophila group with D-GAL, the levels of both the GSH and MDA varied significantly. Our findings showed that the extract of Gypsophila could be used in reducing the oxidative stress during the aging. © 2023 Elsevier B.V., All rights reserved.
Keywords: Aging; D-galactose; Gypsophila perfoliata; lipid peroxidation